Farmer’s routine endurance challenge for UMP volunteers - Muhamad Firdaus, Azman; Nurnatasha Eizreena Atiqah, Abdullah (2017)
It is normal to test physical endurance with outdoors activities such as hiking or long distance cycling, but for 20 students from InSmartive they choose to test their endurance by experiencing the life as a breeder in a three days program of Semaian Budi Project.